Perbaikan Kualitas Layanan Menggunakan Model Hibrid Analisis Big Data: Kasus Restoran Barbeque Korea AYCE - Sukwadi, Ronald; Halim, Williem; Thu, Nguyen Thi Bich (TEKNIK, 2022)
The culinary industry continues to develop every year. One of the phenomena is all you can eat (AYCE) Korean BBQ restaurant. This will cause increasingly intense competition in the restaurant business. The aims of this study are to identify customer needs, to determine the priority of the service attributes, and to provide appropriate suggestions to AYCE Korean BBQ restaurant. The big data analysis using LDA method was applied to determine customer needs based on the Zomato review. The results showed that ten customer needs are identified as Voice of Customer (VOC) for HOQ of the Quality Function Deployment (QFD). The results of the AHP showed that 5 priorities of improvement strategies. The appropriate suggestions for Korean BBQ restaurant are to create a layered control system and customer satisfaction surveys, to implement FIFO and LIFO systems, to check the condition of raw material storage equipment, to improve existing service SOPs, and to provide periodic briefings and training.